1973
DOI: 10.1088/0034-4885/36/2/002
|View full text |Cite
|
Sign up to set email alerts
|

Hydromagnetics of rotating fluids

Abstract: This article reviews work on the dynamics of a rapidly rotating electrically conducting fluid in the presence of a corotating magnetic field. While the separate action of either rotation or a magnetic field produces strong dynamical constraints, their simultaneous action can result in comparatively weak net constraints and novel phenomena then arise. A systematic account of these phenomena is given and certain applications to natural systems (with emphasis on the dynamics of the Earth's liquid core) are outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(139 citation statements)
references
References 133 publications
4
135
0
Order By: Relevance
“…The magneto-rotational instability could operate in regions of the Sun where angular velocity decreases outward from the rotation axis (as it does in the polar regions). Balbus & Hawley (1994) showed that the strong local stratification of the tachocline limits displacements to horizontal surfaces, as expected; this could provide a source of unaccounted for latitudinal momentum mixing in the polar regions.…”
Section: Stability Of the Slow Tachocline Modelssupporting
confidence: 66%
See 2 more Smart Citations
“…The magneto-rotational instability could operate in regions of the Sun where angular velocity decreases outward from the rotation axis (as it does in the polar regions). Balbus & Hawley (1994) showed that the strong local stratification of the tachocline limits displacements to horizontal surfaces, as expected; this could provide a source of unaccounted for latitudinal momentum mixing in the polar regions.…”
Section: Stability Of the Slow Tachocline Modelssupporting
confidence: 66%
“…But the situation may in fact be much worse. In the tachocline, the magnetic Prandtl number is of the order of ν/η ∼ 10 −2 ; if a small-scale dynamo indeed operates at these values of the magnetic Prandtl number (Boldyrev & Cattaneo 2004) magnetic energy accumulates somewhere on the turbulent inertial range and reaches equipartition well before the larger scale field does. This process could quench the turbulent magnetic diffusivity for much lower field strengths (Cattaneo & Vainshtein 1991).…”
Section: Discussion and Prospect For The Dynamo Confinement Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to familiarize the reader with it, we first demonstrate that they easily yield a number of classical results, see e.g. (Acheson & Hide 1973;Acheson 1978).…”
Section: Connection To Known Stability and Instability Criteriamentioning
confidence: 99%
“…It should further be noted that the ratio of the magnetic to kinetic energy for slow MC waves scales like (Acheson and Hide 1973)…”
Section: Magnetic-coriolis Wavesmentioning
confidence: 99%